2005
DOI: 10.1038/nature03517
|View full text |Cite
|
Sign up to set email alerts
|

Strong polarization enhancement in asymmetric three-component ferroelectric superlattices

Abstract: calreticulin/LDL receptor-related protein co-complex stimulates random and directed cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 1 publication
3
72
1
1
Order By: Relevance
“…Most of the dielectric loss comes from conductivity loss. The equivalent resistance in multilayer thin films is equal to that in each layer, which reduces the dielectric loss of multilayer thin films [31].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the dielectric loss comes from conductivity loss. The equivalent resistance in multilayer thin films is equal to that in each layer, which reduces the dielectric loss of multilayer thin films [31].…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] A variety of approaches have been implemented to elucidate the effects of chemical heterogeneity in ferroelectric thin films. 11,12,[14][15][16][17][18][19][20][21][22][23] The majority of these have demonstrated some degree of enhancement to ferroelectric response, in addition to interesting polarization interactions and thermodynamic properties, such as unusual phase change sequences and nonergodicity. 13,14 Experimental approaches, including discrete heterolayers, graded compositions, bi-and tri-layer superlattices, and other fabrication approaches have been employed to study interactions between dissimilar phases and layers in ferroelectric thin films.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,19,23 However, while functional response enhancements are often reported, the mechanisms by which such enhancements are derived are somewhat debated. 10,11,13,14,17,20,24,25 While the origins of response enhancement are perhaps multifaceted and not unequivocally elucidated, the fact remains that the overwhelming majority of these reports has concentrated on single-layer films with unique B-site cation (Zr/Ti) gradients, or unique bi-layers of rhombohedral and tetragonal compositions. 12 Work by Mangalam et al, demonstrated nearly coherent strain in PZT R/T bi-layered and graded thin films, contributing to asymmetric bias profiles in the films, thereby resulting in increased tolerance to strain relaxation and enhanced ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…I n the past decade, there has been a surge of research interest in several types of multilayered/heterolayered ferroelectric thin films consisting of ferroelectric layers of different compositions and structures. Indeed, the resulting ferroelectric behaviors can be tailored by sequential combination of different ferroelectric layers, whereby there can occur a strong coupling and interaction at the interface 1–5 . Several unique ferroelectric phenomena and transitions have been observed with these heterolayered thin films.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling and interactions between neighboring layers can trigger field‐induced strains and ferreoelectric transitions, leading to an increase in polarization and shift in Curie temperature 10–18 . Indeed, a strong improvement in polarization was shown in association with local structure asymmetry and large lattice strain in the supperlattice structures consisting of CaTiO 3 , BaTiO 3 , and SrTiO 3 layers 3 . In addition, some of these heterolayers and superlattices have demonstrated a number of other electrical and optical behaviors 4,19 .…”
Section: Introductionmentioning
confidence: 99%